Association analysis of dopaminergic degeneration and the neutrophil-to-lymphocyte ratio in Parkinson’s disease - Zhang, Fengjiao; Chen, Bin; Ren, Wenhua; Yan, Yayun; Zheng, Xiaoqi; Jin, Shuxian; Chang, Ying (Frontiers in Aging Neuroscience, 2024)
Introduction Peripheral inflammatory responses are suggested to play a major role in the pathophysiology of Parkinson’s disease (PD). The neutrophil-to-lymphocyte ratio (NLR), a new recognized biomarker, can reflect peripheral inflammation in PD. However, the association between the NLR and dopaminergic degeneration in PD remains unclear. Methods In this retrospective study, 101 enrolled PD patients were categorized into early-stage and advanced-stage PD based on the Hoehn and Yahr (HY) scale. We evaluated the clinical characteristics, peripheral immune profile, and 11C-CFT striatal dopamine transporter (DAT) binding levels. Linear regression analyses were employed to assess the associations between NLR and striatal DAT levels at different stages in PD patients. Results Covariate-controlled regression analysis revealed that higher NLR was significantly associated with lower DAT levels in the caudate (β = −0.27, p = 0.003) and the putamen (β = −0.27, p = 0.011). Moreover, in the early-stage PD subgroup, a similar association was observed (caudate: β = −0.37, p = 0.013; putamen: β = −0.45, p = 0.005). The lymphocytes count was correlated positively with the striatal DAT levels in the Spearman correlation analysis whether in total patients (caudate: ρ = 0.25, p = 0.013; putamen: ρ = 0.22, p = 0.026) or in the early-stage subgroup (caudate: ρ = 0.31, p = 0.023, putamen: ρ = 0.34, p = 0.011). Conclusion Dopaminergic degeneration is associated with peripheral inflammation in PD. The NLR, a widely used inflammatory marker, may have the potential to reflect the degree of dopaminergic degeneration in individuals with early-stage PD.